Strong summability of two-dimensional Vilenkin – Fourier series - Goginava, U. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
We study the exponential uniform strong summability of two-dimensional Vilenkin – Fourier series. In particular, it isproved that the two-dimensional Vilenkin – Fourier series of a continuous function $f$ is uniformly strongly summable to afunction $f$ exponentially in the power 1/2. Moreover, it is proved that this result is best possible.